Multistep Testing Algorithms for Clostridioides difficile Infection - Nicholson, Maribeth R; Donskey, Curtis J (JAMA : the journal of the American Medical Association, 2023)
A 10-year-old girl with spina bifida and neurogenic bowel hospitalized for abdominal pain, dehydration, and more than 20 episodes of diarrhea per day. A stool sample test result was positive for Clostridioides difficile by polymerase chain reaction and an enzyme immunoassay result for C difficile toxin A and B was negative. How do you interpret these test results?